The preponderance and dye-tissue receptive variability analyses of malignant and benign lesions of the female genitalia - F.M. Onyije; A.A. Ngokere; O.O. Mgbere; A.E. Ligha (Journal of Oncological Sciences, 2017)
Background: Benign and malignant lesions of the female genitalia are of great concern worldwide. The roles of dyes to aid identification of diagnosis in these two classes of lesions are of importance. The aim of this research was to determine the prevalence of malignant and benign lesions in the female genitalia and their receptivities to seven histochemical dyes. Materials and Methods: Six hundred and thirty two (n = 632) gynaecological malignant and benign lesions data collected from the archives of the Histopathology Laboratory of Braithwaite Memorial Specialist Hospital (BMSH), Port Harcourt, Nigeria between 2010 and 2014 were used for this study. The representative tissues were sectioned and stained with Haematoxylin and Eosin (H&E), Masson's Trichrome (MT), Periodic Acid Schiff (PAS), Phosphotungstic Acid Haematoxylin (PTAH), Southgate Mucincamine (SGM), Alcian Blue (AB) and Verhoeff Van Gieson (VVG) dyes. Results: We identified 601 (95.1%) benign and 31 (4.9%) malignant lesions during the 5-year period. The mean and standard deviation (±SD) of patients' age associated with the malignant and benign tissues were 47.7 ± 16.7 and 37.3 ± 11.2 years. There were significant (p < 0.05) associations in the distribution of lesions by age category, reproductive status, region, and origin of tissue, but not by year of diagnosis and developmental stage (p > 0.05). Stain analyses revealed significant variations in the receptivity of the seven dye-tissues with the mean % area for benign lesions ranging from 38.94 ± 10.60% in SGM to 64.51 ± 12.04% in MT and those of malignant lesions ranging from 37.64 ± 17.71% in AB to 63.95 ± 8.94% in MT. Similarly, intensity measurements for benign lesions ranged from 81.76 ± 13.96 points (pts) in MT to 161.39 ± 17.23 pts in AB compared to malignant lesions, which ranged from 78.04 ± 25.73 pts in MT and 167.75 ± 12.62 pts in AB. Conclusion: Our study reported the preponderance of benign lesions than malignant lesions in the sample population. Comparatively, MT exhibited the best dye-tissue receptivity in both benign and malignant lesions than the baseline dye (H&E) and remains a valuable tool for the diagnosis of gynecological lesions.